Development of an Immunochromatographic Strip Using Conjugated Gold Nanoparticles for the Rapid Detection of Klebsiella pneumoniae Causing Neonatal Sepsis - Noha M. Elhosseiny; Tamer M. Samir; Aliaa A. Ali; Amani A. El-Kholy; Ahmed S. Attia (MDPI AG, 2021)
Neonatal sepsis is a leading cause of death among newborns and infants, especially in the developing world. The problem is compounded by the delays in pinpointing the causative agent of the infection. This is reflected in increasing mortality associated with these cases and the spread of multi-drug-resistant bacteria. In this work, we deployed bioinformatics and proteomics analyses to determine a promising target that could be used for the identification of a major neonatal sepsis causative agent, Klebsiella pneumoniae. A 19 amino acid peptide from a hypothetical outer membrane was found to be very specific to the species, well conserved among its strains, surface exposed, and expressed in conditions simulating infection. Antibodies against the selected peptide were conjugated to gold nanoparticles and incorporated into an immunochromatographic strip. The developed strip was able to detect as low as 105 CFU/mL of K. pneumoniae. Regarding specificity, it showed negative results with both Escherichia coli and Enterobacter cloacae. More importantly, in a pilot study using neonatal sepsis cases blood specimens, the developed strip selectively gave positive results within 20 min with those infected with K. pneumoniae without prior sample processing. However, it gave negative results in cases infected with other bacterial species.